2017
DOI: 10.1016/j.scitotenv.2016.10.156
|View full text |Cite
|
Sign up to set email alerts
|

Cross-ecosystem fluxes: Export of polyunsaturated fatty acids from aquatic to terrestrial ecosystems via emerging insects

Abstract: Cross-ecosystem fluxes can crucially influence the productivity of adjacent habitats. Emerging aquatic insects represent one important pathway through which freshwater-derived organic matter can enter terrestrial food webs. Aquatic insects may be of superior food quality for terrestrial consumers because they contain high concentrations of essential polyunsaturated fatty acids (PUFA). We quantified the export of PUFA via emerging insects from a midsize, mesotrophic lake. Insects were collected using emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 65 publications
(25 reference statements)
7
84
1
2
Order By: Relevance
“…However, because individual predatory Perlidae stoneflies are relatively large, the total amount of DHA in a Perlidae stonefly may still be profitable for in‐stream or riparian predators from a foraging efficiency perspective. In general, our findings for DHA are also consistent with previous findings in other predatory emergent insects, such as dragonflies (Popova et al, ) and phantom midges ( Chaoborus flavicans ; Martin‐Creuzburg, Kowarik, & Straile, ).…”
Section: Discussionsupporting
confidence: 92%
“…However, because individual predatory Perlidae stoneflies are relatively large, the total amount of DHA in a Perlidae stonefly may still be profitable for in‐stream or riparian predators from a foraging efficiency perspective. In general, our findings for DHA are also consistent with previous findings in other predatory emergent insects, such as dragonflies (Popova et al, ) and phantom midges ( Chaoborus flavicans ; Martin‐Creuzburg, Kowarik, & Straile, ).…”
Section: Discussionsupporting
confidence: 92%
“…However, primary consumers in both systems were found to have very similar body N:P ratios, suggesting that N may be available in excess for aquatic consumers, leading to elevated N:P excretion/egestion ratios (Elser et al, ). Higher nutrient or fatty acid availability in the donor ecosystem also may increase the nutrient or fatty acid content in the body tissues of animal consumers in that ecosystem, with subsequent effects on the quality of their excretion/egestion and carcasses (Heintz et al, ; Small & Pringle, ; Twining et al, ; Martin‐Creuzburg, Kowarik & Straile, ). Animals' diet in the donor ecosystem also may interact with animals' body stoichiometry, as an animal with a low body N:P ratio feeding on a diet with a high N:P ratio will have to consume more food to obtain sufficient P, thus excreting a larger amount of N (Vanni, ).…”
Section: Donor Ecosystem Characteristicsmentioning
confidence: 99%
“…Provision of complementary resources may be more likely when the donor and recipient ecosystems differ substantially from one another. For example, because aquatic and terrestrial systems often differ in stoichiometry and limiting resources, inputs that move from an aquatic ecosystem into a terrestrial ecosystem, or vice versa , may be more likely to provide different resources than those already available in the recipient ecosystem (Elser et al, ; Nowlin, Vanni & Yang, ; Sitters et al, ; Twining et al, ; Martin‐Creuzburg et al, ).…”
Section: Recipient Ecosystem – Physical/chemical Characteristicsmentioning
confidence: 99%
“…Total export of EPA+DHA from the aquatic ecosystem by amphibians in our study was greater than values reported for three anurans emerging from a Russian lake (1.47 mg/m 2 ; Yermokhin et al., ). Amphibians exported LC‐PUFAs to the terrestrial ecosystem at levels comparable to aquatic insect emergence in several systems (Borisova et al., ; Gladyshev, Kharitonov, et al., ; Gladyshev, Sushchik, Yurchenko, et al., ), but the amount of EPA, DHA, and ARA exported from aquatic systems may be driven by the community composition of emerging taxa, and hydroperiod (Martin‐Creuzburg, Kowarik, & Straile, ; Moyo et al., ; Sushchik et al., , ). The importance of emerging aquatic insects for riparian predators has been well documented (as reviewed by Baxter et al., ; Richardson, Zhang, & Marczak, ).…”
Section: Discussionmentioning
confidence: 99%